2018
DOI: 10.3390/molecules23061496
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Essential Oil and Lipid Fraction from the Aerial Part of Bupleurum scorzonerifolium Willd. (Apiaceae) from Different Habitats

Abstract: The essential oils and lipid fraction extracted from the aerial parts of Bupleurum scorzonerifolium were determined by a GC-MS method. In total, up to 67 components were identified. cis-β-Ocimene, trans-β-ocimene, limonene, α-pinene, α-copaene, β-elemene, and caryophyllene oxide were recognized as consistent components of the essential oil extracted from the aerial parts of B. scorzonerifolium, regardless of the habitat. The content of these components varied from traces to a significant amount. The volume of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
1
14
0
2
Order By: Relevance
“…It should be pointed out that the high content of ketone nonadecanone-10 was identified in both species. This compound was also previously identified in plants of other species: B. bicaule, B. sibiricum [ 15 ], and B. scorzonerifolium [ 16 ]. High content of unsaturated FAs, including oleic and linoleic acids, the amount of which was up to 59.12%, provides the pharmacological value of these species.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…It should be pointed out that the high content of ketone nonadecanone-10 was identified in both species. This compound was also previously identified in plants of other species: B. bicaule, B. sibiricum [ 15 ], and B. scorzonerifolium [ 16 ]. High content of unsaturated FAs, including oleic and linoleic acids, the amount of which was up to 59.12%, provides the pharmacological value of these species.…”
Section: Resultsmentioning
confidence: 63%
“…It is suggested that the final form of the plant, including lipid profile, in our view, is determined by the genotype and epigenetic factors [ 26 ]. So, FAs compositions of B. scorzonerifolium from different habitats and years of collection [ 16 ] did not have an impact on the group classification of perennial and annual plants, but it reflected the rather high intraspecific variability of the FAs composition, which is comparable with the level of variability at the interspecific level in other groups ( Figure 1 and Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Наибольшим разнообразием входящих в состав эфирных масел соединений отличается фаза цветения. [3], что также подтверждается и данными настоящего исследования. Стоит отметить, что из вышеупомянутых соединений только три -транс-β-оцимен, лимонен и β-элемен -встречаются во все фазы развития, то есть они являются константными для эфирных масел B. scorzonerifolium вне зависимости от места произрастания и фазы вегетации.…”
Section: обсуждение результатовunclassified
“…В Китае, Корее и Японии является официнальным растением и успешно используется в качестве противовоспалительного, жаропонижающего, желчегонного, тонизирующего, стимулирующего средства [1,2]. Есть сведения о составе эфирных масел и липидной фракций растений этого вида, произрастающих на территории Забайкалья, Монголии и Китая [3]. В литературе также имеется ряд работ: изучен состав флавоноидов нескольких видов володушек, в том числе B. scorzonerifolium флоры Бурятии [4], исследованы фенольные соединения, эфирные масла, элементный состав володушки козельцелистной, произрастающей в Прибайкалье [5][6][7][8][9][10][11].…”
Section: Introductionunclassified